2016
DOI: 10.1111/vop.12419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of auriculopalpebral nerve block on Schirmer tear test I values in normal horses

Abstract: There was no effect of auriculopalpebral nerve block on STT I values in normal horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Despite the difference among the species, this result is also similar to the one found by Honsho et al (2014), who observed that ropivacaine 0.75% showed a greater and more lasting tear production reduction when compared to bupivacaine, when used in retrobulbar block in humans. However, in a study by Visser et al (2017) evaluating tear production after auriculopalpebral nerve block with lidocaine 2% in horses, increased values were observed in the Schirmer tear test, although not significant.…”
Section: Discussionmentioning
confidence: 82%
“…Despite the difference among the species, this result is also similar to the one found by Honsho et al (2014), who observed that ropivacaine 0.75% showed a greater and more lasting tear production reduction when compared to bupivacaine, when used in retrobulbar block in humans. However, in a study by Visser et al (2017) evaluating tear production after auriculopalpebral nerve block with lidocaine 2% in horses, increased values were observed in the Schirmer tear test, although not significant.…”
Section: Discussionmentioning
confidence: 82%
“…In this study Hannah Visser and colleagues in the USA compared Schirmer tear test I (STTI) values collected in normal horses with and without an auriculopalpebral nerve block .…”
Section: Auriculopalpebral Nerve Blocksmentioning
confidence: 99%
“…Altering eyelid function may impact measured ocular parameters, and the effect of AP nerve block on equine Schirmer tear test I has recently been investigated . Similarly, it is postulated that reduction of eyelid muscle tone and resistance could lower measured IOP in animals with eyelid motor nerve blocks .…”
Section: Introductionmentioning
confidence: 99%
“…Altering eyelid function may impact measured ocular parameters, and the effect of AP nerve block on equine Schirmer tear test I has recently been investigated. 24 Similarly, it is postulated that reduction of eyelid muscle tone and resistance could lower measured IOP in animals with eyelid motor nerve blocks. 1,2,5,18 Specifically, AP nerve blocks ' impact on equine tonometry as measured with applanation tonometry (Tono-Pen ® ) has been assessed for this consideration and was found to have no significant effect.…”
Section: Introductionmentioning
confidence: 99%